Utilization of nonguideline concordant antibiotic treatment following acute otitis media in children in the United States. Issue 2 (2nd November 2022) - McGrath, Leah J.; Frost, Holly M.; Newland, Jason G.; O'Neil, Caroline A.; Sahrmann, John M.; Ma, Yinjiao; Butler, Anne M.
Abstract: Purpose: Acute otitis media (AOM) is a common indication for antibiotics in children. We sought to characterize the frequency of nonguideline concordant antibiotic therapy for AOM in the United States, by agent and duration. Methods: Using national administrative claims data (2016–2019), we identified children aged 6 months to 17 years with an oral antibiotic dispensed within 3 days of a new diagnosis of suppurative AOM. Use of nonguideline concordant agents and durations, defined based on national treatment guidelines, were summarized by age, race, rurality, region, and insurance type. Subsequent oral antibiotic dispensing within the year after AOM diagnosis was also evaluated. We created sunburst diagrams to visualize longitudinal patterns of within‐person antibiotic utilization for AOM, by agent and duration. Results: We identified 789 424 eligible commercially‐insured and 502 239 medicaid‐insured children. Among commercially insured children, 35% received nonguideline concordant agents for AOM, including cefdinir (16%), amoxicillin‐clavulanate (12%), and azithromycin (7%). Fewer children age <2 years received a nonguideline concordant initial agent (27%) compared to age ≥6 years (41%). More children age <2 years received three or more antibiotics over the following year (34% vs. 3% for children age ≥6 years). The most common treatment duration was 10 days for all ages; treatment duration for the initial antibiotic was nonguideline concordant for 95% and 89% of children age 2–5 years and ≥6 years, respectively. Patterns were similar for medicaid‐insured children. Conclusions: Nonguideline concordant antibiotic use is common when treating AOM in children, including use of broad‐spectrum agents and longer‐than‐recommended antibiotic durations.